Mechanism of Addition of Methanol to Mestilyiminopropadienone - Shtaiwi, Majed; Elgamal, Y.M.A.; Alomary, Ahmed (Asian Journal of Chemistry, 2012)
The addition of methanol to the mesityliminopropadienone compound A were studied by using 1H NMR spectra which shows a complicated kinetics involving a fast reaction to about 35 % consumption followed by slow one. Consideration of the kinetics behaviours under different experimental conditions at 10 ºC and the product assignment provide valuable mechanistic insight into the system studied. The stoichiometry was observed to be 1:1 in terms of mesityliminopropadienone and methanol consumed and therefore, the overall order for the reaction is second order and the product formed was malonic ester amide (malonamate) D.